ANALYSIS OF EFFECT PERCEIVED OF RISK AND PERCEIVED OF REPUTATION ON PURCHASE DECISION ON COSMETICS ONLINE SHOPING - Leksono, Puji; Novawiguna, Novawiguna (Universitas Mercu Buana, 2021)
Abstract.This study aimed to analyze the influence of perceived of risk and perceived of reputation for Cosmetics Online purchasing decisions with Trust as an intervening variable.Both factors are expected to be taken into consideration for online businesses to build relationships with customers. The subjects of this study are women, internet users who have ever shopped online at least one times in online shoppingsite’s amounted to 113 people. The research instrument was a questionnaire used to measure the perception of respondents using a Likert scale. Data collection procedures carried out through a survey of female where given a questionnaire with closed model (respondents' answers alternative has been provided). All instruments were tested for validity and reliability and has been qualified as an analytical tool. Analysis was performed using SPSS statistical methods. The results of the measurement of Influence of perceived of Risk, Perceived Reputation and Trust in Purchase Decision, Shows that trust has a positive effect 3.411 and significant 0.001on purchasing decisions, The perception of the risk of a negative effect (-1636) but not significant 0.105, effect positive perception of the reputation of a significant 3376 and 0.001 on purchasing decisions cosmetics online.Perceived of Risk , Perceived of Reputation and Trust together have positive and significant effect on the Buying Decision cosmetics onlineAbstrak . Penelitian ini bertujuan untuk menganalisis pengaruh persepsi risiko dan persepsi reputasi terhadap keputusan pembelian Kosmetik secara online dengan Kepercayaan sebagai variabel Intervening. Kedua faktor tersebut di harapkan menjadi bahan pertimbangan bagi pelaku usaha online dalam membangun relasi terhadap konsumen. Subyek penelitian ini adalah wanita, pengguna internet di Indonesia yang pernah berbelanja online minimal satu kali di situs belanja online berjumlah 113 orang. Instrumen penelitian berupa kuesioner yang digunakan untuk mengukur persepsi responden menggunakan skala likert. Prosedur pengumpulan data dilakukan melalui survey terhadap wanita dimana diberikan kuesioner dengan model tertutup (alternative jawaban responden telah disediakan ). Seluruh instrumen penelitian diuji validitas dan reliabilitasnya dan telah memenuhi syarat sebagai alat analisis. Analisis yang dilakukan menggunakan metode statistic SPSS. Hasil pengukuran Pengaruh Persepsi Risiko, Persepsi Reputasi dan Kepercayaan terhadap Keputusan Pembelian, menunjukkan bahwa kepercayaan berpengaruh positif 3.411 dan signifikan 0.001 terhadap keputusan pembelian, persepsi resiko berpengaruh negative (-1.636 ) namun tidak signifikan 0.105, persepsi reputasi berpengaruh secara positif 3.376 dan signifikan 0.001 terhadap keputusan pembelian kosmetik secara online.Persepsi Risiko, Persepsi Reputasi dan Kepercayaan secara bersama-sama berpengaruh positif 78.602 dan signifikan0.000 terhadap Keputusan Pembelian kosmetik secara online .